Economic analysis of the water demand in the hotels and restaurants sector: Shadow prices and elasticities. Issue 8 (15th August 2014) - Angulo, Ana; Atwi, Majed; Barberán, Ramón; Mur, Jesús
Abstract Despite the growing economic importance of tourism, and its impact on relative water shortage, little is known about the role that water plays in the productive process of hotels and restaurants and, therefore, the possible implications of water demand management policy for this sector. This study aims to fill this gap. It is based on the microdata of 676 firms in the sector, operating in the city of Zaragoza (Spain) for a 12 year period. Based on the Translog cost function, we estimate the shadow price of water in the short run and, from a long‐run perspective, its direct price elasticity, its cross elasticities relative to labor, capital, and supplies, and its elasticity with respect to the level of output. The results obtained show that water provides sector firms returns that are on average higher than its price, although in the case of hotels the margin is really narrow. This situation provides policy makers with a margin for applying price increases without affecting the sector's viability, with some caution in the case of hotels. Water demand elasticity equals −0.38 in the case of hotels, but it is not significant in the case of restaurants and bar‐cafes; hence, only in hotels is there potential for influencing water use patterns, encouraging the resource's conservation through pricing policy. Moreover, capital is a substitutive factor of water, and the elasticity of water with respect to output is 0.40, all of which should also be considered by policy makers in water resource management.